Statutory Recognition Provisions in Britain, 1976-1980 - Beaumont, P. (Relations industrielles / Industrial Relations, 1983)
This paper assesses the extent to which the union movement in Great Britain was able to realise in practice the potential advantages of the statutory recognition provisions.